A COMPARATIVE STUDY OF ACADEMIC ACHIEVEMENT OF PRIVATE AND GOVERNMENT SENIOR SCHOOL STUDENT IN MEERUT DISTRICT - Daud, Shubha; Kumar, Munendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present learns to scrutinize differences in academic achievement in village and city student of school. Educational success plays a pivotal role in whole formation of a child. In India academic achievement is considered important to get admission in good school. The future success in career also plays an essential role in getting on the right place with right people. When we talk about the school in government and private setting their journey to academic achievement is considered different. In this world of self-sufficiency everyone is racing to get there whether it is a village school boy/ girl or a city boy/girl both in this journey faces their own difficulty. The study was conducted on 300samples (150government and 150private) of class 11thin the Meerut District. The result indicates inconsequential variation has been found in the scholastic success between pastoral and build-up school boy student in senior secondary school. It has been about the same in the educational achievement between rustic and town school girl student.